(untitled) (GYMNASIUM, 2008)
The attitude of society towards people with disabilities has continuously changed along time and it was not a favourable one to these people. The first attempts of the society to „treat ” in a certain way children and adults with disabilities were of a medicat kind and they were in fact their internment in hospitals and asylums. So, along history, disabled children were usually isolated in specialized institutions that were meant to protect disabled children and society at the same time.